PMO-194 Polypoid lesions in the UGI tract in patients with portal hypertension; EUS before you biopsy!. (28th May 2012) - Shams, A; McAvoy, N; Alexandridis, S; Plevris, J; Hayes, P
Abstract : Introduction: The universal use of upper gastrointestinal (UGI) endoscopy in patients with portal hypertension in combination with increasing number of patients with liver disease has resulted in the detection of indeterminate upper GI lesions, other than obvious varices. Many of these lesions are found incidentally and biopsying them presents a dilemma for the endoscopists, as this may lead to serious complications. The aim of this retrospective study was to assess the nature of such lesions using endoscopic ultrasound (EUS) prior to a biopsy. Methods: A total of 22 consecutive patients with portal hypertension who underwent an EUS evaluation between June 2008 and November 2011 for upper GI polypoid lesions found on endoscopy were included in the study. Procedure and pathology reports, obtained from patients' electronic records, were reviewed. Results: Of the 22 patients (16 men, 6 women, median age 66) who underwent upper GI endoscopy, 11 had lesions in the proximal stomach (gastro-oesophageal junction, fundus, gastric body) while eight had lesions in the distal stomach (antrum, pylorus) and three in the duodenum. Six (27.3%) proved to be varices and 4 (18.2%) polypoid lesions over varices (2 benign, 2 malignant). Whereas, 7 (31.8%) patients had true polyps. The remaining lesions found on EUS included 1 (4.5%) case of gastric fold, 1 gastric antral vascular ectasia (GAVE), one ulcer, 1 case of external compression and one patient had a normal EUS with no lesion seen. Of the 10 cases of varices and varices underlying polypoid lesions, 8 (80%) were in the proximal stomach. Histology of non-vascular lesions under EUS were available in 11 patients, which showed 5 (45.5%) inflammatory polyps, 2 (18.2%) adenocarcinoma, 2 (18.2%) adenoma, 1 (9.1%) normal and one was reported as insufficient sample. Conclusion: Indeterminate upper GI lesions encountered during routine endoscopy in patients with portal hypertension are commonly either varices or may develop around varices. We recommend EUS evaluation prior to biopsying such lesions in order to avoid potential serious complications such as iatrogenic variceal bleed. Competing interests: None declared.